A Single Methylene Group in Oligoalkylamine‐Based Cationic Polymers and Lipids Promotes Enhanced mRNA Delivery. Issue 33 (4th July 2016) - Jarzębińska, Anita; Pasewald, Tamara; Lambrecht, Jana; Mykhaylyk, Olga; Kümmerling, Linda; Beck, Philipp; Hasenpusch, Günther; Rudolph, Carsten; Plank, Christian; Dohmen, Christian
Abstract: The development of chemically modified mRNA holds great promise as a new class of biologic therapeutics. However, the intracellular delivery and endosomal escape of mRNA encapsulated in nanoparticles has not been systematically investigated. Here, we synthesized a diverse set of cationic polymers and lipids from a series of oligoalkylamines and subsequently characterized their mRNA delivery capability. Notably, a structure with an alternating alkyl chain length between amines showed the highest transfection efficiency, which was linked to a high buffering capacity in a narrow range of pH 6.2 to 6.5. Variation in only one methylene group resulted in enhanced mRNA delivery to both the murine liver as well as porcine lungs after systemic or aerosol administration, respectively. These findings reveal a novel fundamental structure–activity relationship for the delivery of mRNA that is independent of the class of mRNA carrier and define a promising new path of exploration in the field of mRNA therapeutics. Abstract : Oligoalkylamine‐based lipids and polymers were generated and screened for buffering capacity and mRNA delivery. Alternating ethylene/propylene/ethylene spacers in the tetramines improve transfection efficiency (see picture, middle) over ethylene‐only (left) or propylene‐only repeats (right). This trend is valid regardless of delivery platform (lipids or polymers), tested cell line, targeted tissue, or application route in vivo.